Treatment of infant colic with craniosacral therapy. A randomized controlled trial - Mercedes Castejón-Castejón; M.A. Murcia-González; J Todri; O Lena; R Chillón-Martínez (Elsevier, 2022)
Objective: To evaluate the number of craniosacral therapy sessions that can be helpful to obtain a resolution of the symptoms of infantile colic and to observe if there are any differences in the evolution obtained by the groups that received a different number of Craniosacral Therapy sessions at 24 days of treatment, compared with the control group which did not received any treatment. Methods: Fifty-eight infants with colic were randomized into two groups of which 29 babies in the control group received no treatment and those in the experimental group received 1-3 sessions of craniosacral therapy (CST) until symptoms were resolved. Evaluations were performed until day 24 of the study. In this study crying hours served as primary outcome. The secondary outcome were the hours of sleep and the severity, measured by an Infantile Colic Severity Questionnaire (ICSQ). Results: Significant statistical differences were observed in favor of experimental group compared to the control group on day 24 in crying hours (mean difference = 2.94, at 95 %CI = 2.30-3.58; p < 0.001) primary outcome, and also in hours of sleep (mean difference = 2.80; at 95 %CI = − 3.85 to − 1.73; p < 0.001) and colic severity (mean difference = 17.24; at 95 %CI = 14.42-20.05; p < 0.001) secondary outcomes.Also, the differences between the groups ≤ 2 CST sessions (n = 19), 3 CST sessions (n = 10) and control (n = 25) were statistically significant on day 24 of the treatment for crying, sleep and colic severity outcomes (p < 0.001). Conclusion: Babies with infantile colic may obtain a complete resolution of symptoms on day 24 by receiving 2 or 3 CST sessions compared to the control group, which did not receive any treatment.